(NoSNOWY TEORII KOLEBANIJ (B:s (Nu^EBNOE POSOBIE (B/s - (NmIGULIN(B, (NwLADIMIR wASILXEWI^s; (NmEDWEDEW(B, (NwLADLEN iOSIFOWI^s; (NmUSTELX(B, (NeLENA rUDOLXFOWNAs; (NpARYGIN(B, (NwLADIMIR nIKOLAEWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1978)
(NbIBLIOGR(B.: (NS (B392 (19 (NNAZW(B.)s
Keywords: (NkOLEBANIQs -- (Nu^EBNIKI I POSOBIQs